The word at work from A to Z - Van Horne, Marion; Brook, Larry (Quezon City New Day Publishers, 1998)
A collection of helpful, interesting and instructive hints for the practice of writing as a craft, it serves as an inspirational and informative tool for those concerned with the methods and techniques of communicating effectively.
Purpose: "A compilation of the best of the material contained in the 100 issues of The Word at Work (title of book)."
Content/s: Selected articles from The Word at Work.
Original ed. published in 1993 by David C. Cook Foundation.
Keywords: Authorship -- Handbooks, manuals, etc